Sea Ice as Enemy and Friend: The Case of Iceland and Labrador - Ogilvie, Astrid (Arctic Portal, 2011)
Dr. Astrid Ogilvie, CICERO, Centre for International Climate and Environmental Research, Oslo, talks here in the NRF 6th open assembly in Hveragerði, Iceland, in September of 2011. Please click on the link above to see the video.